Determination of the Active Lenticel Numbers in Some Types and Varieties Fruit - ERSOY, NILDA; CETIN, HILAL; KANKAYA, ABDULLAH; KARAKUS, AYDIN (Asian Journal of Chemistry, 2010)
The losses in products like loss of weight in fruit and vegetables, wilting wizening, the structure of the lenticels intensity on the surface of the fruit is important. The more the lenticels and other openings on fruit surface are the faster the metabolic phenomena such as respiration, transpiration, etc. Fruit samples belonging to Braeburn, Granny Smith, Starkrimson Delicious, Golden Delicious (apple), Angeleno, Globe Sun, October Sun, TC Sun (plum), Esme (quince) varieties were used in the experiment to determine their active lenticels numbers. The number of lenticels on unit surface, which provide the connection between interior and exterior environments on epidermis, was found to be between 12.96 and 19.96 depending on the types and varieties used in the experiment. When the differences between the numbers of lenticels on the whole surfaces of apple, plum and quince varieties are taken into account, the highest value belongs to the Breaburn (242.9 number/fruit) apple variety whereas the lowest value belongs to TC Sun plum (56.6 number/fruit) variety.